Oxide and Organic–Inorganic Halide Perovskites with Plasmonics for Optoelectronic and Energy Applications: A Contributive Review - Brahim Aïssa (14157243) (2021)
The ascension of halide perovskites as outstanding materials for a wide variety of optoelectronic applications has been reported in recent years. They have shown significant potential for the next generation of photovoltaics in particular, with a power conversion efficiency of 25.6% already achieved. On the other hand, oxide perovskites have a longer history and are considered as key elements in many technological applications; they have been examined in depth and applied in various fields, owing to their exceptional variability in terms of compositions and structures, leading to a large set of unique physical and chemical properties. As of today, a sound correlation between these two important material families is still missing, and this contributive review aims to fill this gap. We report a detailed analysis of the main functions and properties of oxide and organic–inorganic halide perovskite, emphasizing existing relationships amongst the specific performance and the structures. Other Information Published in: Catalysts License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/catal11091057